ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO INVESTASI SAHAM - Pramana, I B Agung; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
This study aims to prove the effect of interest rate, the rupiah against the US dollar, capital structure, operating leverage and liquidity of the company against the risk of stock investments. The research sample was determined by purposive sampling method nine issuers automotive and component industries in automotive and component industries in Indonesia Stock Exchange with the observation period of five years from 2010-2014. Data were analyzed using multiple linear regression, determination, F test and t test. Results of the study are: the interest rate on deposits negative effect on the risk of investing in stocks, the rupiah against the US dollar has no effect on the risk of equity investment, capital structure a positive influence on the risk of stock investments, operating leverage has no effect on the risk of stock investments, and liquidity of the company is not influence on the risk of stock investments.
Keywords: Factor Macro, Micro, Stock Investment Risk.